2013
DOI: 10.1016/j.athoracsur.2012.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Fluorine-18 Fluorodeoxyglucose-Positron Emission Tomography in Management Strategy for Thymic Epithelial Tumors

Abstract: Results. The mean SUVmax was 4.5 (range, 1.2 to 14.6) and was significantly higher for Masaoka stage IV than for I and II (all p < 0.008) and for World Health Organization classified thymic cancer compared with all other types (all p < 0.0001). Mean SUVmax revealed signifi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…Similarly, the authors reported a significant difference comparing TNM stages III-IV vs. I-II and identified an optimal cut-off of 5.6. Comparable results were described by Matsumoto et al [ 33 ], who reported a significantly higher SUVmax for Masaoka Koga stage IV compared to stages I-II and for large tumours (>60 mm) compared with small tumours (<60 mm). Conversely in the study by Fukumoto et al [ 34 ], the SUV difference comparing Masaoka Koga stage III-IV vs. I-II raised statistical significance ( p = 0.06).…”
Section: The Role Of 18 F-fdg Pet/ct In Thymic Epithelial Tumourssupporting
confidence: 78%
“…Similarly, the authors reported a significant difference comparing TNM stages III-IV vs. I-II and identified an optimal cut-off of 5.6. Comparable results were described by Matsumoto et al [ 33 ], who reported a significantly higher SUVmax for Masaoka Koga stage IV compared to stages I-II and for large tumours (>60 mm) compared with small tumours (<60 mm). Conversely in the study by Fukumoto et al [ 34 ], the SUV difference comparing Masaoka Koga stage III-IV vs. I-II raised statistical significance ( p = 0.06).…”
Section: The Role Of 18 F-fdg Pet/ct In Thymic Epithelial Tumourssupporting
confidence: 78%
“…Several previous studies have shown that the maximum standardized uptake value (SUVmax) determined using 18 F-FDG-PET is useful for predicting the WHO grade of malignancy in thymic epithelial tumors. 6,7 Although the majority of previous studies examined the relationship between SUVmax and histology, Matsumoto et al 8 reported that SUVmax was significantly higher for large tumors than for small tumors. To avoid the effect of tumor size on SUVmax, we hypothesized that the ratio of SUVmax to tumor size is a clinically useful measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Discordant results were reported previously about the utility of SUVmax and/ or SUVmean for differentiation between two of these TETs or groups probably due to small study populations and different proportions of histological types in individual studies. [11][12][13]15,16,26 Treglia et al 38 performed a meta-analysis of SUVmax and demonstrated statistically significant differences in SUVmax between low-and high-risk thymomas, and between low-risk or highrisk thymomas and thymic cancers, although a SUVmax cut-off for discriminating between groups could not be defined due to the large overlap of these semi-quantitative values among the different TETs.…”
Section: Discussionmentioning
confidence: 99%
“…10 18 F-FDG PET has recently emerged as a tool for grading histological types and staging of TETs. [11][12][13][14][15][16] More recently, PET image texture analysis was proposed to characterize the heterogeneity of tumour 18 F-FDG uptake. 17 Tumour 18F-FDG uptake is usually heterogeneous.…”
mentioning
confidence: 99%